Risks and cost estimates: the disconnect - Byrne, G (Mine Closure 2024: 17th International Conference on Mine Closure, 2024)
Many mine closure plans these days appropriately include a risk assessment. This is often driven by corporate and regulatory pressures to have a risk basis for closure plans. Unfortunately often these risk assessments sit in isolation to the rest of the closure plan and often do not feed into the closure strategy and proposed actions. Importantly, very few are incorporated into the closure cost estimates. Identifying and quantifying risks is critical to the closure planning process because of the inherent uncertainties associated with closure planning, which is often undertaken many years or even decades before the cessation of mining activities. Therefore, a comprehensive and representative risk assessment which can then form the basis for closure risk costs to be estimated and included as part of the overall closure cost estimate is required. A proper understanding of the likely closure costs cannot be obtained without understanding the closure risks. These risks are many and varied but can be broadly grouped with respect to costs. The first group comprises those risks associated with uncertainties relating to the planned closure activities, such as quantities and unit rates (termed ‘uncertainty risk’). The second group of risk costs is that associated with ‘risk events’; that is, things that are not certain to occur but could have a material impact on the closure cost if they occur. The first group could be addressed by applying a contingency factor to the cost estimate. Percentage contingencies are widely used for project cost estimates in industry as, being simple and easily understood, they have a high level of acceptance. They are, however, a very crude measure of uncertainty and do not directly relate to each specific cost line item. Percentage contingencies are not appropriate to address the second group — risk events. Unfortunately, all too often the risk costs represented by such events are either ignored or assumed to be covered by a contingency. A preferable system is to adopt a two-fold approach to cost estimating using range analyses to reflect uncertainties regarding items such as quantities and unit rates as well as a more detailed estimate of the likelihoods/consequences of risk events. Each approach can use either deterministic or probabilistic evaluation techniques with the latter, it is argued, thereby presenting a more robust and defensible cost estimate.
Keywords: closure risk; risk assessments; risk cost; closure planning; contingency